KLEMENT VON METTERNICH AND HIS INFLUENCE ON EUROPEAN POLITICS - Діденко, Катерина (Modern engineering and innovative technologies, 2023)
The work examines the history of the Austrian Empire in the international arena in the first half of the 19th century. The activity of Clemens Wenzel Lothar von Metternich-Oxenhausen in the position of chancellor of the European state is analyzed. Achieve